Handbook of research on international consumer law - Howells, Geraint G.; Ramsay, Iain; Wilhelmsson, Thomas, 1949-; Edward Elgar Publishing (Cheltenham : Edward Elgar Publishing, 2018)
Consumer law and policy continues to be of great concern to both national and international regulatory bodies, and the second edition of the Handbook of Research on International Consumer Law provides an updated international and comparative analysis of the central legal and policy issues, in both developed and developing economies. Taking a thematic approach, and yet highlighting issues in different national contexts, the Handbook explores issues which are common to all countries, such as social policy and effective business regulation, and relates consumer law to contemporary trends in human rights law. Features of this edition: consideration of the potential for new regulatory complexity as a result of Brexit; reflections on the growth of middle class consumption in Asia and Latin America and the impact that this will have on business reforms; coverage of increasing divergence between the regulatory models of both the EU and the US; focus on the challenges and opportunities that the digital age presents for consumer market regulation; analysis of the significant changes in consumer credit law and policy since the financial crash of 2008. This Handbook will provide researchers, students and policymakers with an insight to the main policy debates in differing national and sectoral contexts, and provide models of legal regulation which contribute to the evaluation and development of consumer laws and policy.
Preface -- 1. Consumer law in its international dimension / Geraint Howells, Iain Ramsay and Thomas Wilhelmsson -- 2. Consumer protection and human rights / Iris Benöhr and Hans-W. Micklitz -- 3. Development and consumer law / Sothi Rachagan -- 4. The consumer and competition law / Angus MacCulloch -- 5. Misleading and unfair advertising / James P. Nehf -- 6. Protecting rational choice: information and the right of withdrawal / Christian Twigg-Flesner, Reiner Schulze and Jonathon Watson -- 7. Unfair terms and standard form contracts / Thomas Wilhelmsson and Chris Willett -- 8. Sales and guarantees / Cynthia Hawes and Christian Twigg-Flesner -- 9. Products liability law in America and Europe / Geraint Howells and David G. Owen -- 10. Product safety regulation / Luke Nottage -- 11. Consumers and services of general interest / Peter Rott and Chris Willett -- 12. Consumer protection and the Internet / Patrick Quirk and John A. Rothchild -- 13. Regulation of consumer credit / Iain Ramsay -- 14. Personal insolvency / Johanna Niemi -- 15. What next for the financial consumer: More disclosure? Caveat Vendor? Fin-tech online? / Dimity Kingsford Smith and Olivia Dixon -- 16. Access to justice / Kate Tokeley -- 17. Using class actions to enforce consumer protection law / Deborah R. Hensler -- 18. Enforcing consumer protection law / Colin Scott -- Index.
Obsahuje bibliografie, bibliografické odkazy a rejstřík
Elektronická reprodukce.
Keywords: ochrana spotřebitele; srovnávací právní věda; consumer protection; comparative law; e-knihy online; e-books online